“Aku Cinta Diriku secara Rasional dan Spiritual”: Tinjauan Pustaka Sistematis tentang Self-Love dalam Perspektif Islam dan Barat - Hani Fadilah Humaira; Fuad Nashori (Al-Qalb : Jurnal Psikologi Islam, 2026)
Abstract: This study aims to determine the similarities and differences of self-love in the perspective of Islamic psychology and Western psychology as well as its synthesis and application in a modern context. The method used is PRISMA (Preferred Reporting Items for Systematic Reviews and Analyzes). The sources of literature used are Scopus, Mendeley, and Garuda. The limitations of the reviewed journals are research using Indonesian and English, spanning the years 2020-2025, and research in the form of articles with the keywords "self-love", "self-love", "Islamic Psychology", "Islamic perspective", "Quranic view", "Islamic psychology", "Islamic perspective", "Quranic view", "Western Psychology", "Psychology", "western psychology", and "Psychology". Based on the results of the review, eight articles were found that were in accordance with the research objectives. The results of the study found that self-love is a multidimensional concept that is adapted according to cultural values and religiosity in society. In the perspective of Islamic psychology, self-love is part of worship and has spiritual value. While in the perspective of Western psychology, self-love is focused on the psychological and social well-being of individuals. The synthesis of both shows that the concept of complete self-love should include personal, social, and spiritual dimensions to make individuals healthy rationally and spiritually.